Association Between Premature Ejaculation and Religious Orientation - Sari Motlagh, Reza; Sari Motlagh, Nayyer; Shenasi, Reihan; Kafi Kang, Amirreza; Roshandel, M.Reza (Archives of Men’s Health, 2021)
Introduction: Premature ejaculation (PE) is the most common male sexual dysfunction. Although its etiology is not fully understood, several organic and psychological disorders have been identified as risk factors. The main aim of this study is to find any association between religious orientation (RO) and PE. Methods: We designed a cross-sectional study and 80 participants with PE as the main chief complaint were enrolled. After filling informed consent, all participants have filled two questionnaires including the Premature Ejaculation Diagnostic Tool (PEDT) for PE and the Allport & Ross intrinsic-Extrinsic Religious Orientation Scale for RO assessment respectively. Spearman’s rho analysis was used for assessing the association between PEDT scores and ROS scores by SPSS 22.0 version. Results: Out of 80 patients with mean age 35.56 ± 8.46 years, 70 patients (87.5%) had PEDT positive score. Of them, 45 (64%) had lifelong PE and 25 (36%) experienced an acquired PE. Correlation analysis was shown a reverse correlation between PEDT positive scores and Intrinsic RO (P = 0.05) with a correlation coefficient -0.311, PEDT positive and negative scores was not correlated with extrinsic RO (P= 1). Conclusion: Patients with a lower intrinsic religious orientation score have a higher probability for PE and PEDT positive score.